Towards an efficient approach using graph-based evolutionary algorithm for IoT botnet detection - Ngo, Quoc-Dung; Nguyen, Huy-Trung (Informatica, 2023)
In recent years, a large number of Internet of Things devices are used in life, many of which are vulnerable to attacks from a security perspective. Botnet malware is one of the main threats to IoT devices. Hence detection of IoT botnet is one of the most important challenge for IoT devices. This paper proposes an IoT botnet detection approach base on PSI graph data combine with evolutionary algorithm-based technique. To the best of our knowledge, there have been no studies that used evolutionary algorithms to support detecting multi-architecture IoT botnet. The proposed method has achieved good experimental results (i.e., 95.30%). The approach also achieves a relatively low false-positive rate at 4.59%.